Stem cell-based strategies for intervertebral disc regeneration in degenerative microenvironments: challenges and solutions - Wang, Honglin; Xu, Aoshuang; Hua, Wei; Mao, Junling; Zhang, Jiyao; Ma, Xiaobo; Lu, Lin (Frontiers in Cell and Developmental Biology, 2025)
Low back pain (LBP) is a common musculoskeletal disorder, and its pathological basis is closely related to intervertebral disc degeneration (IVDD). Although commonly used conservative treatments and surgical interventions can alleviate symptoms, they are difficult to fundamentally delay or reverse the process of IVDD. In recent years, biological treatment strategies centered on cell therapy, targeting the initiating mechanisms of IVDD, have provided new directions for the fundamental treatment of this disease. Among them, mesenchymal stem cells (MSCs) are regarded as ideal candidate cell types for achieving intervertebral disc regeneration due to their immunomodulatory properties and multidifferentiation potential. The discovery of endogenous stem cells within the intervertebral disc further reveals the tissue’s own repair potential. As the “soil” upon which “seed” cells depend for survival, the intervertebral disc microenvironment, composed of cell niches and their surrounding biochemical and physical factors, plays a key regulatory role in the proliferation, differentiation, and functional expression of stem cells and endogenous cells. However, the intervertebral disc is naturally in extreme conditions such as low oxygen, low nutrition, acidic pH, and high mechanical load. This microenvironment further deteriorates during the degeneration process, not only severely affecting the survival and function of resident cells but also posing severe challenges for stem cell transplantation therapy. This article systematically reviews the characteristics of the intervertebral disc microenvironment under physiological and degenerative states, focusing on the impact of the degenerative microenvironment on the biological behavior of stem cells. It summarizes key strategies for enhancing MSC adaptability and therapeutic efficacy and proposes standardized parameters for optimizing clinical applications, aiming to provide a theoretical basis and path support for advancing the clinical translation of stem cell therapy in intervertebral disc regeneration.